The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1161/circgenetics.111.960773
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Expression Signature That Classifies Human Atherosclerotic Plaque by Relative Inflammation Status

Abstract: Background-Atherosclerosis is a complex disease requiring improvements in diagnostic techniques and therapeutic treatments. Both improvements will be facilitated by greater exploration of the biology of atherosclerotic plaque. To this end, we carried out large-scale gene expression analysis of human atherosclerotic lesions. Methods and Results-Whole genome expression analysis of 101 plaques from patients with peripheral artery disease identified a robust gene signature (1514 genes) that is dominated by process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 49 publications
2
61
0
Order By: Relevance
“…We hypothesized that dysregulation of expression of NTN1 and its receptors associate with atherosclerosis and plaque stability in vivo. Using recently published macrophage and SMC signatures, 16 we studied the expression of NTN1 and its receptors in circulating monocytes and human(s) atherosclerotic plaque samples in vivo and their potential association with plaque stability.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesized that dysregulation of expression of NTN1 and its receptors associate with atherosclerosis and plaque stability in vivo. Using recently published macrophage and SMC signatures, 16 we studied the expression of NTN1 and its receptors in circulating monocytes and human(s) atherosclerotic plaque samples in vivo and their potential association with plaque stability.…”
Section: Circ Cardiovasc Genetmentioning
confidence: 99%
“…Therefore, these genes were selected for differential expression and correlation analyses. 16 were used in the hierarchical clustering analysis to assess whether subgroups of samples had similar marker profiles as well as whether NTN1 and UNC5B showed similar expression levels across the samples. The procedure was performed using the heatmap.2 function from the gplots R library using all 92 artery samples.…”
Section: Microarray Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that in the atherosclerotic lesion, densely populated with cholesterol-enriched macrophage foam cells, SMPDL3A expression will also be significantly raised. In support of this hypothesis, microarray analysis of human carotid atherosclerotic plaque tissue by other groups has indicated that SMPDL3A forms part of a gene expression signature that is indicative of inflamed foam cellrich plaque tissue (38), and SMPDL3A is the fifth most up-regulated mRNA in symptomatic (unstable) plaque tissue obtained from carotid endarterectomy patients (39). Furthermore, our re-analysis of publicly available microarray expression data using the NCBI GEO database and GEO2R tool (40) (accession number GSE21419) reveals that Smpdl3a mRNA is significantly up-regulated in laser-capture microdissected atherosclerotic plaques from apoE Ϫ/Ϫ mice, versus the adjacent healthy adventitial tissue (41,42).…”
Section: Discussionmentioning
confidence: 87%
“…The inflammatory state of plaque macrophages was shown to be dynamically regulated as the severity of disease varied 144 . In humans, studies using LCM on surgical plaque explants has also identified genes implicated in lipid metabolism (such as FABP4 and LEP) and activation of the adipokine/peroxisome proliferator-activator receptor (PPAR) signalling pathways 145 , as well as a repertoire of inflammatory gene 'signatures' 146 , that might be important in mechanistic staging. Early findings utilizing this approach seem to corroborate observations from genome-wide association studies as well as plaque compositional changes in plaque revealed by highresolution MRI Chai, personal communication.…”
Section: Molecular Techniques-mentioning
confidence: 99%